Micro and Meso Discourse Analysis on Arabic Vocabulary Videos Based TikTok from Fairclough's Perspective - Winda Nur Lathifah; Singgih Kuswardono; Khaldi Hicham (PPPBA, 2024)
The trend of utilizing technology in education enhances the achievement of learning objectives. TikTok's presence fosters innovation in Arabic language learning. This study employs Norman Fairclough's theory, analyzing microstructural (vocabulary, sentences, lexical meaning) and mesostructural (discourse production and consumption) discourse. The goal is to critically analyze Arabic language learning videos on TikTok. This qualitative research uses TikTok videos and netizen comments. Data collection methods included observation, basic tapping techniques, and advanced SLC with note-taking. Validity techniques were consistent observation and time extension. Instruments included the researcher, data cards, and recapitulation sheets. The study analyzed 20 video samples with 752 words and 128 sentences. Vocabulary analysis found 2 collocation groups and 10 set groups. Sentence classification based on communication context identified 15 interrogative, 45 declarative, 6 exclamatory, and 20 imperative sentences. Sentence structure classification found 5 argumentative, 1 exposition, 1 descriptive, and no narrative texts. Lexical analysis identified 150 nouns, 23 adjectives, and 46 verbs. Content production varied by account type. Text consumption analysis revealed diverse comment models: interest, criticism, suggestions, and interactions between netizens and content creators. Continuously creating engaging Arabic learning content on TikTok can boost public interest and dispel the stigma that Arabic is difficult.